2020
DOI: 10.3390/met10020160
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ultrasonic Soldering of AlN Ceramics with Copper Substrate Using Zn–Al–Mg Solder

Abstract: This research aims to develop the direct soldering of aluminum nitride (AlN) ceramics with a copper substrate using Zn–Al–Mg solder. The solder type, Zn5Al3Mg, has a close-to eutectic composition with a melting point of 359 °C. The microstructure of Zn–Al–Mg solder is composed of solid solution (Al), solid solution (Zn), an Mg2Zn11 phase and a minority MgZn2 phase. The tensile strength is from 82 to 169 MPa and depends on the magnesium content. The bond with AlN ceramics is formed due to the interaction of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To improve the wettability of ceramic material with Zn-Al-Mg solder, soldering with the assistance of active ultrasound was employed. The tensile strength of Zn-Al-Mg soldering alloys ranges from 82 to 169 MPa; the highest strength was observed in the solder with the lowest Mg content [10] .…”
Section: Figure 1 Ultrasound Effects In Liquid Media and Their Applicationmentioning
confidence: 99%
“…To improve the wettability of ceramic material with Zn-Al-Mg solder, soldering with the assistance of active ultrasound was employed. The tensile strength of Zn-Al-Mg soldering alloys ranges from 82 to 169 MPa; the highest strength was observed in the solder with the lowest Mg content [10] .…”
Section: Figure 1 Ultrasound Effects In Liquid Media and Their Applicationmentioning
confidence: 99%
“…It is also to be noted that in modern power module circuits and assemblies, various metallic conductors are also needed to be joined to the ceramic dies and circuits [12][13][14]. Various authors have suggested the use of active metal soldering and/or brazing or low-temperature Zn-based soldering [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Wetting may be achieved by metallization of the substrate surfaces prior to the joining process [11], but an alternative, frequently used approach is adding chemically active elements, most commonly Ti, Zr and Hf to the solder alloy [12][13][14][15]. Furthermore, the use of Mg [16][17][18], V [19,20], Ta [21,22], Cr [23], Nb [24] and rare earth elements such as La [25,26] and Lu [27] is also reported in the literature. Wetting with the aid of active elements is associated with their enrichment at the substrate/solder interface, reaction with the substrate and consequently the formation of a reaction phase layer [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%